Perioperative outcomes of open surgical repair for juxtarenal and infrarenal aortoiliac occlusive disease in patients with poor cardiac status - S K Balaji; C Saravanan Robinson; Sudharsan Reddy Yalamuru; Sabarish G Kumar; Adharsh Kumar Maruthupandian; Syed Mohammed Ali Ahmed; M V Bharat Arun; Ruru Ray (Indian Journal of Vascular and Endovascular Surgery, 2022)
Purpose: The most common cause of mortality in patients undergoing open surgical repair for aortoiliac disease is from cardiac complications. As there is a paucity of literature about the surgical outcomes in patients with compromised cardiac status, this study was undertaken to study the perioperative outcomes of open surgical repair for aortoiliac occlusive disease in patients with poor cardiac status. Methodology: A retrospective study was carried out from January 2017 to December 2020. Patients with aortoiliac occlusive disease based on computed tomography angiographic findings with poor cardiac reserve (ejection fraction ≤40% on echocardiography) were included in the study. The primary endpoints were perioperative complications which included intraoperative hemodynamic complications and early postoperative complications. Results: During 2017–2020, a total of 44 patients with aortoiliac occlusive disease (AIOD) with erectile function ≤40% underwent open surgical repair. Of these, 25 (57%) patients had infrarenal aortoiliac involvement and 19 (43%) had juxtarenal aortoiliac involvement. In our study of open surgical repair for juxtarenal and infrarenal aortoiliac occlusive disease in patients with poor cardiac status, intraoperative hemodynamic complications were noted in 26 (59%) patients, early postoperative complications were noted in 11 (25%), and mortality rate was 4.5%. Conclusion: Even though AIOD patients with poor cardiac status are at high operative risk than patients with normal cardiac status, open surgical repair with in-line bypass can be considered as a suitable option in these patients, especially where facilities for appropriate intraoperative monitoring and management are available.